Answer:
f(q)=1.77q+47,738
Step-by-step explanation:
Step 1: Subtract 3x from both sides.
−x+7=−52
Step 2: Subtract 7 from both sides.<span><span><span><span>
−x</span>+7</span>−7</span>=<span><span>−52</span>−7</span></span><span><span>
−x</span>=<span>−59</span></span>
Step 3: Divide both sides by -1.<span><span><span>
<span><span>−x</span><span>−1</span></span></span></span>=<span><span><span><span>−59</span><span>−1</span></span></span></span></span><span>
x=59</span>
Answer:
1
Step-by-step explanation:
√12
√10
√5
divide all by 6
Y=-3x+1
So the answer is A. All you're doing is moving the 3x to the opposite side, and because your switching the side, you need to switch the sign. So it's a negative 3x after you solve for y. Solving for y(or any letter) is just getting that letter alone on one side of the equal sign.